Enhanced NOAA chemical reactivity worksheet for determining chemical compatibility. Issue 1 (5th August 2013) - Gorman, Dave; Farr, Jim; Bellair, Rob; Freeman, Wade; Frurip, Dave; Hielscher, Al; Johnstone, Harold; Linke, Myriam; Murphy, Pat; Sheng, Min; van, Klaas; Viveros, Dalina
<x xml:space="preserve">Abstract</x> As a result of a two‐year joint effort between the National Oceanic and Atmospheric Administration (NOAA) and The Dow Chemical Company, an enhanced version (3.0) of the NOAA Chemical Reactivity Worksheet now is available. In addition to addressing previously identified limitations with version 2.0 of this tool, several enhancements have been incorporated into the tool to help with the generation and presentation of chemical compatibility charts. This article covers the development and use of this new tool, highlighting the enhancements that position this tool to become the gold standard within the chemical industry for determining chemical compatibility. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 4–18, 2014